Determinação do grau de pureza de amostra de crack apreendidas no Estado da Paraíba por RMNq-1H e CLAE-DAD - Costa, Rony Anderson Rezende (2012)
Population´s commonsense regards crack cocaine as an impure byproduct of cocaine. In Brazil, the cocaine levels in crack samples or the profiling of its adulterants is not a mandatory analysis of official forensic laboratories. The state of Paraiba has shown a marked increase in the number of analyses done on crack cocaine samples seized by the police forces between 2007 and 2010, rising from 250 to 575 analyses. On the other hand, there is no literature data on the concentration of cocaine on these samples. The present study aimed at developing and validating a method based on quantitative hydrogen nuclear magnetic resonance spectroscopy (1H-qNMR) to determine cocaine in crack cocaine samples seized within the state of Paraiba. 1H-qNMR is a primary analytical method and can become accurate and precise when certain acquisition and processing parameters are properly set. The 1H-qNMR method was compared to a high performance liquid chromatography method with photodiode array detection (HPLC-PDA). The results from both methods allowed us to determine that the average concentration of cocaine in the samples was higher than 70%. The average concentration determined by the 1H-qNMR method was 71.9%, with samples ranging from 5.2 to 89.1%. The results from the HPLC-PDA method were slightly higher, with an average figure of 74.4% and samples ranging from 4.9 to 93.8%. The best correlation between HPLC-PDA and 1H-qNMR data was obtained when integration from region 7 of the spectrum was used (singlet signal at 3.6 ppm from the methyl protons of the ester function) yielding a Pearson´s correlation coefficient of 0.83. Precision and accuracy of the 1H-qNMR method was sensitive to several acquisition and processing parameters that need to be optimized. The HPLC-PDA method developed proved to be fast, accurate and precise for the quantification of cocaine in 47 samples of seized crack cocaine. In addition, the analysis of crack cocaine samples by gas chromatography coupled to mass spectrometry (GC/MS) revealed that the main adulterant present in the samples was phenacetin, a result that was confirmed by the 1H-NMR data.